Cytotoxicity of folic acid conjugated hollow silica nanoparticles toward Caco2 and 3T3 cells, with and without encapsulated DOX - Patel, Kunal; Sundara Raj, Behin; Chen, Yan; Lou, Xia (2016)
© 2016 Elsevier B.V. Hollow silica nanoparticles of two sizes with and without a folic acid targeting ligand were synthesized. Fickian diffusion of the antitumor drug doxorubicin hydrochloride (DOX) was demonstrated by the produced nanoparticles, achieving a cumulative release of 73% and 45% for 215nm and 430nm particles respectively over a period of 500h. The hollow silica nanoparticles presented a time and dose dependent toxicity, selective to human epithelial colorectal adenocarcinoma (Caco2) cells, over mouse embryonic fibroblast (3T3) cells. At 24h Caco2 cell viability was reduced to 66% using pure hollow silica at a concentration of 50µgmL-1, while that of 3T3 cells remained at 94% under the same conditions. The selective cytotoxicity of hollow silica nanoparticles was further enhanced by conjugation of folic acid and incorporation of DOX: at 24h and an equivalent DOX concentration of 0.5µgmL-1, viable Caco2 cells were reduced to 45% while 3T3 cells were reduced to 83%. Interestingly the equivalent dose of free DOX was more toxic to 3T3 than to Caco2 cells, reducing the 3T3 viability to 72% and the Caco2 viability to 80%, which is likely due to the presence of the p-glycoprotein pumps in Caco2 cells. Folic acid conjugation served to enhance the viability of both cell lines in this work. Careful optimization of the folate content should further improve the cell specificity of the hollow silica nanoparticles, thus providing a viable targeting platform for cancer therapy.